2006
DOI: 10.1021/bi051786m
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine 387 and Arginine 404 Are Critical in the Hydrolytic Mechanism of Escherichia coli Aminopeptidase P

Abstract: Analysis of the pH-rate profile for catalysis of bradykinin cleavage by aminopeptidase P (AMPP), a manganese-containing hydrolase from Escherichia coli, was carried out to show that optimal catalytic function is obtained at neutral pH. On the basis of information derived from the crystal structure, peptidase sequence alignments, and the hydrolysis of organophosphate triesters, active site residues Arg153, Arg370, Trp88, Tyr387, and Arg404 were identified as potential catalytic residues. Site-directed mutagenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…The expression and purification of His-tagged E. coli AMPP and its mutants have been described in [4] [13]. The proteins were purified from BL21(DE3) cells according to the methods therein.…”
Section: Experimental Partmentioning
confidence: 99%
“…The expression and purification of His-tagged E. coli AMPP and its mutants have been described in [4] [13]. The proteins were purified from BL21(DE3) cells according to the methods therein.…”
Section: Experimental Partmentioning
confidence: 99%
“…1). In aminopeptidase P from E. coli Tyr387 has been proposed to be involved in the conserved hydrogen-bond network in the Asp260-Arg404-Tyr387 motif, which is able to shuttle a proton from the bulk solvent to the leaving peptide (Jao et al, 2006). Moreover, it was also suggested that Tyr387, Arg404 and His350 are important residues for proline specificity (Wilce et al, 1998;Graham et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was also suggested that Tyr387, Arg404 and His350 are important residues for proline specificity (Wilce et al, 1998;Graham et al, 2006). Site-directed mutagenesis of Tyr387 and Arg404 resulted in a severalfold reduction in the activity of aminopeptidase P from E. coli (Jao et al, 2006). From this viewpioint, structural and functional characterization of XPD43 from X. campestris is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Proline aminopeptidase (PAP) is therefore required to remove the proline residues and is essential for the degradation of proline-rich peptides and proteins, such as collagen and gelatin [6]. The crystal structure and catalytic mechanism of the proline aminopeptidase from Escherichia coli has been reported [7,8]. The genus Streptomyces was proved to be a good source of various substrate-specific aminopeptidases such as leucine or methionine aminopeptidase [9,10].…”
Section: Introductionmentioning
confidence: 99%